Exosomes: Novel Bio-Inspired Nanocarriers for Efficient Targeting of Glioblastoma Tumor Cells - V Taghdiri Nooshabadi (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: Glioblastoma is a highly malignant brain tumor that is characterized by poor prognosis and high recurrence rate in patients. Surgery, chemotherapy and radiotherapy are considered as standard methods of glioblastoma treatment. However, these methods have not been able to completely kill cancer cells. One of the most important barriers to the treatment of glioblastoma is the blood-brain barrier, which prevents drugs from reaching the brain tissue. The aim of this study was to investigate the possibility of using exosomes as drug carriers in the treatment of glioblastoma tumor. METHODS: In this review article, we searched Google Scholar and Pub Med databases using the keyword “exosomes”, “glioblastomas”, and “drug delivery systems” to provide an overview of exosomes as an opportunity for the delivery of drug into the central nervous system through the blood-brain barrier. FINDINGS: In the initial search, 14400 articles were found, and after an initial review and removal of unrelated studies, 40 articles were finally reviewed. Exosomes are natural nanoparticles that are secreted from different cells. Using exosomes in drug delivery systems is an efficient approach for transferring various contents to cancer cells. These particles are also able to transfer biological and drug molecules from the blood-brain barrier to brain cells. These natural nanoparticles are stable with long circulations that do not cause immune rejection responses. CONCLUSION: According to the results of this study, as a potential carrier with very interesting and attractive advantages in drug delivery and transfer of drug agents, exosome-based nanocarriers can be used to treat brain tumors such as glioblastoma multiforme.